Analisis Kebutuhan Air Bersih Perumda Tirta Ogan Kabupaten Ogan Ilir Dan Perencanaan Jaringan Perpipaan Dengan Bantuan Perangkat Lunak Epanet 2.2 - Anugroho, Rohmat; Sahbar, Robi; Pujiono, Pujiono (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The need for clean water as a primary requirement for survival demands effective management in terms of the volume and standard of water that can be used. The clean water needs assessment plan was designed using a case study approach, taking into account population projections and estimated water consumption in Ogan Ilir Regency until 2034. Basic and additional data collection is one of the methods used, as is population estimation through the application of geometric and arithmetic methodologies. The arithmetic approach estimates the need for clean water at 45,035,981 m³/day (WHO), 19,815,831 m³/day (PUPR), and 21,617,271 m³/day (SNI) based on a projected population of 496,071 people in 2034; The geometric approach estimates the clean water requirement at 45,266,478 m³/day (WHO), 19,917,250 m³/day (PUPR), and 21,727,909 m³/day (SNI). By using EPANET 2.2 software, which can simulate the hydraulic system of clean The assessment of water distribution and the performance of the pipeline design is reinforced through a technical analysis of the distribution system